Fishes of the Cocos (Keeling) Islands: new records, community composition and biogeographic significance - Hobbs, Jean-Paul; Newman, Stephen; Mitsopoulos, G.; Travers, M.; Skepper, C.; Gilligan, J.; Allen, G.; Choat, H.; Ayling, A. (Raffles Museum of Biodiversity Research, 2014)
The Cocos (Keeling) Islands comprise the most isolated oceanic atoll in the tropical Indian Ocean and are situated 1000 km south-west of Indonesia. The remoteness of the islands has shaped the composition of marine communities but also limited scientific research. This study summarises field research on the marine fishes of the Cocos (Keeling) Islands over the last 14 years (2001–2014). Sixty-seven new records (from 28 families) are described and raise the total number of known fishes to 602 species from 84 families. New records span a variety of body sizes (3 cm TL Gobiodon unicolor to 500 cm TL Rhincodon typus), were observed in all major habitats,and found at both the Southern Atoll and at North Keeling Island. Notable new records include first records for the families Alopiidae, Coryphaenidae, Eleotridae, Gempylidae, Istiophoridae, Molidae, Polymixiidae, Rhincodontidae, Sillaginidae and Xiphiidae. Sampling from pelagic and deepwater (60–300 m) reef environments significantly increased the number of species described from these habitats. New records include species that have dispersed more than 2500 km (Centropyge acanthops) and dispersal ability appears to explain the lack of syngnathids and the high representation of acanthurids and holocentrids in the community. Some of the Indian Ocean species that have colonised the Cocos (Keeling) Islands now co-occur with their Pacific Ocean sister species, increasing the potential for hybridisation. Although the fish community of the Cocos (Keeling) Island resembles that of the Indo-West Pacific, the isolation and co-occurrence of Indian and Pacific Ocean species distinguishes it from all other locations.